The Problem of Providing Legal Groundwork for the Balance of Traditional and Alternative Energy Development in the Context of Kazakhstan’s Shift to Green Energy - NUREKESHOV, Talap; MUKASHEVA, Anar; BEKISHEVA, Sabigul; KHASSENOV, Muslim (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
This paper focuses on the problem of providing legal groundwork for the balance of traditional and alternative energy development in the context of the Republic of Kazakhstan’s shift to green energy. As it turns out, there is no comprehensive strategy for providing legal groundwork for the use of energy, both traditional and renewable. Today there are two major standpoints among both scientists and experts on the ground: for and against the renewable sources. Thus, the main task of lawyers is to develop an approach that makes both sides agree on the issue. The paper performs an analysis of Kazakhstan’s legislation on energy development, energy preservation and the use of renewable energy sources, identifying its shortcomings and gaps. The attained results provide a basis for recommendations to create a legal regulatory framework for the development of traditional and alternative energy in the Republic of Kazakhstan, as well as to improve environmental legislation in terms of environmental protection during construction, location and use of traditional and alternative energy facilities.